2004
DOI: 10.1017/s1478951504040209
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of Dignity Psychotherapy delivered via telemedicine

Abstract: Telemedicine can greatly extend the benefits of Dignity Psychotherapy by bringing it to patients who are dying at home. Our very preliminary work suggests that delivering the intervention to patients who are too ill to leave their homes or who are in rural locations may be a feasible way to help them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 25 publications
1
40
0
3
Order By: Relevance
“…25 Finally, there was a study on DT’s feasibility via telemedicine. In the study, they concluded that telemedical DT is feasible because the problems that appeared were easily solved 12 (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…25 Finally, there was a study on DT’s feasibility via telemedicine. In the study, they concluded that telemedical DT is feasible because the problems that appeared were easily solved 12 (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…Research into conducting the intervention via email and through videoconferencing is also indicated. There has been one small study with eight participants showing dignity therapy can be delivered using videoconferencing [41] but a larger study is warranted. Future studies should include hope as an outcome as well as explore the possible relationship between a person's spirituality and changes to hopefulness through dignity therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Results from several exploratory investigations and trials in Canada, Australia, the UK and US have demonstrated it has the potential to alleviate patients' psychological-existential distress (Passik et al 2004, Chochinov et al 2011, 2012, Montross et al 2011, Hall et al 2012. In Taiwan, psychological-spiritual care offered to terminally ill patients does not yet reach the standard their families expect (Hu et al 1999, Chang et al 2002.…”
Section: Introductionmentioning
confidence: 99%